Система регулирования температурного режима вращающейся печи - Троценко, Л.Н.; Пикашов, В.С. (Энерготехнологии и ресурсосбережение, 2015)
Разработана и внедрена на вращающейся печи для обжига каолина на комбинате по производству огнеупоров система отопления на базе двухпроводной газовой горелки с регулируемой длиной факела мощностью 35 МВт и максимальным расходом природного газа 4 000 м3/ч. Конструкция горелки обеспечивает регулирование длины факела, способствуя достижению требуемого технологическими условиями распределения температуры по длине печи. В систему отопления входит защитно-запальное устройство, система безопасности и регулирования температуры в печи. Во внутренних слоях кладки установлены термодатчики с бесконтактной передачей сигнала к пульту управления. В результате реконструкции среднегодовая экономия природного газа составила 15 - 20 %. Температура газов на выходе из печи уменьшилась на 100 - 200 °C. Благодаря уменьшению разрежения перед дымососом с 1,2 - 1,5 до 0,8 - 1,0 кПа в печи значительно снизился пылеунос, а приведенные к α = 1,0 выход NОx после печи составлял не более 225 мг/м3, СО - 0,019 %. Розроблено та впроваджено на обертовій печі для випалу каоліну на комбінаті з виробництва вогнетривів систему опалення на базі двопровідного газового пальника з довжиною факела, що регулюється, потужністю 35 МВт та максимальними витратами природного газу 4000 м3/год. Конструкція пальника забезпечує можливість регулювання довжини факелу, сприяючи досягненню розподілу температур за довжиною печі відповідно до технологічних умов. У систему опалення входить захисно-запальний пристрій та система безпеки та регулювання температури у печі. У внутрішніх шарах кладки встановлено термодатчики з безконтактною передачею сигналу до пульту управління. У результаті температура газів на виході з печі зменшилася на 100–200 °С. Завдяки зменшенню розрідження перед димососом від 1,2–1,5 до 0,8–1,0 кПа у печі значно знизився пилоунос, а приведений до . = 1,0 вихід NОх після печі становив не більш 225 мг/м3, СО — 0,019 %. New heating system on the basis of the gas burner with adjustable length of the torch with 35 MW capacity and the maximum flow of natural gas to 4000 m3/h was developed and implemented on a rotating kiln of kaolin factory for production of refractories. Air supply is realized by burner of 25–30 % of the total needed for combustion air and supply through the draught of the rest of the air flow, heated in the refrigerator fireclay crumbs to 500–700 °C. The design of the burner provides the ability to control the length of the torch, contributing to the achievement of the required technological conditions of temperature distribution along the length of the furnace. Regulation of the length of flame in the burner is carried out using special gas valve. In the heating system includes also includes protective-ignition device and security system and regulation of temperature in the furnace. To regulate the temperature in the burning zone for the first time in domestic practice of rotary kilns operation in the inner layers of masonry installed sensors with contactless transmission of signal to the control unit via radio, powered by solar batteries. The furnace has a length of 75 m and drum diameter 3,6 m. Temperature in the burning zone is 1450–1500 °С. As a results of industrial tests of new heating system of rotary kiln was reached reduction of natural gas consumption in continuous operation of the furnace up to 30 % at reduction of excess air ratio from 1,1–1,3 up to 1,05–1,1 and depression before vacuum exhauster from 1,2 to 1,5 up to 0,8–1,0 kPa.